TEACHING PROCESSES AND LEARNING STYLES - Obidjonova Gulshoda Otabek qizi; Iminjonova Dilfuza Muzaffarjon qizi; Gaforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The concept of learning style has gained significant importance in the field of education. Many psychologists believe that understanding how students prefer to learn is a crucial factor influencing their academic performance. This study aims to uncover the significance of learning styles in the learning process and evaluate their effectiveness in teaching and learning. The primary objective of the research is twofold: firstly, to investigate the impact of learning styles on the teaching and learning processes, and secondly, to assess key models within various learning environments to comprehend their strengths and weaknesses. By identifying students' learning styles, educators can tailor their instruction to better suit individual needs. This, in turn, enhances the learning experience for students and boosts their self-confidence. Additionally, aligning teaching methods with students' learning styles can generate enthusiasm for the subject, encourage exploration and understanding of facts, and foster a willingness to apply acquired knowledge in practical scenarios.